CINEMA AND PANDEMIC IN INDONESIA: A SOCIOLOGICAL PERSPECTIVE ON ATTITUDES TOWARDS COVID- 19 AND ISOLATION IN A SHORT MOVIE POSITIF BY JEIHAN ANGGA AND HANUNG BRAMANTYO - Yusri Fajar; Nanang Endrayanto; Diah Ayu Wulan (Fakultas Ilmu Budaya, Universitas Mulawarman, 2021)
The COVID-19 epidemic has spurred Indonesian filmmakers to produce films depicting the pandemic's consequences. Positif, a short film on the COVID-19 pandemic directed by Jeihan Angga and Hanung Bramantyo and posted on YouTube on January 1, 2021, has surpassed over two million views. The goal of this film is to raise public knowledge about how to protect themselves from the coronavirus. This article examines how Positif portrays a man who does not believe in the coronavirus and how he eventually must be isolated since he has become infected. I argue that the filmmaker of Positif focuses on delineating the man's unbelief in the coronavirus because it is a problem that Indonesia has had to deal with during the COVID-19 pandemic. This analysis of the film takes a sociological approach, viewing it as a representation of social realities. This article will unpack Positif through textual and contextual analysis. The result shows that the main character in this film, Tegar, does not believe in the coronavirus, and hence refuses to heed his family's and friends' advice. This film emphasizes the repercussions that Tegar must face. He was finally discovered to be positive and was quarantined. Tegar's obstinate refusal to believe in Covid-19 was eventually broken when several Covid-19 positive patients died. As a result, the film's goal is to raise awareness about Covid-19 among Indonesians who disbelieve in it.